Identifying the Dominant Personality Profiles in Medical Students: Implications for Their Well-Being and Resilience - Eley, Diann S.; Leung, Janni; Hong, Barry A.; Cloninger, Kevin M.; Cloninger, C. Robert (PLOS ONE, 2016)
Purpose There is a high prevalence of stress, depression, and burn-out in medical students. Medical students differ widely in personality traits, self-perceptions, and values that may have an impact on their well-being. This study aimed to investigate variability in their personality profiles in relation to their potential for well-being and resilience. Method Participants were 808 medical students from The University of Queensland. An online questionnaire collected socio-demographics and the Temperament and Character Inventory to assess personality traits. Latent profile analyses identified students’ trait profiles. Results Two distinct personality profiles were identified. Profile 1 (“Resilient”) characterized 60% of the sample and was distinguished by low Harm Avoidance combined with very high Persistence, Self-Directedness and Cooperativeness compared to Profile 2 ("Conscientious"). Both Profiles had average levels of Reward Dependence and Novelty Seeking and low levels of Self-Transcendence. Profiles did not differ by age, gender, or country of birth, but rural background students were more likely to have Profile 1. While both Profiles indicate mature and healthy personalities, the combination of traits in Profile 1 is more strongly indicative of well-being and resilience. Conclusions Finding two distinct profiles of personality highlights the importance of considering combinations of traits and how they may interact with medical students’ potential for well-being. Although both profiles of students show healthy personalities, many may lack the resilience to maintain well-being over years of medical training. Programs that develop character and personality self-awareness would enhance their well-being and prepare them to promote the health of their patients.